Skończone Sprężysto-Plastyczne Ugięcia Płyt Kołowo-Symetrycznych - Waszczyszyn, Z. (Engineering Transactions, 1967)
Fundamental geometric and equilibrium equations are derived with a Lagrangian coordinate as an independent variable. The physical equations are assumed in the form obtained by J. R. LEPIK [6] on the grounds of the Hencky-Ilyushin strain theory. The equations become those of small elastic-plastic deflection or the Kármán equations applied for computation of large deflections, depending on the kind of the simplifications introduced. A numerical method is proposed for solving the equations obtained, by means of the semi- inverse method and numerical integration. The paper includes two numerical examples. In the first an annular plate is loaded a by a bending moment uniformly distributed along the outer contour which rests on hinged support. The radial distribution of the internal forces and the displacements is obtained. The results are confronted with the computation results obtained on the grounds of the theory of small deflections. The second example concerns the equilibrium, after buckling, of an annular plate, compressed by a radial load along the outer contour.